Electronic patient-reported outcome systems and capabilities in cancer care: a systematic review - Hosna Salmani; Somayeh Nasiri; Mahdi Alemrajabi; Maryam Ahmadi (Frontiers in Digital Health)
BackgroundCancer care increasingly emphasizes patient-centred approaches, leading to the adoption of electronic patient-reported outcome (ePRO) systems for essential patient data collection. Our systematic review investigates the landscape of electronic patient-reported outcome systems and their capability in cancer care, focusing on their potential to enhance patient-centred solutions.MethodsWe conducted a systematic review, encompassing studies on electronic patient-reported outcomes in cancer. We searched in Scopus, Web of Science, and PubMed using comprehensive Medical Subject Heading (MeSH) terms up to April 2024. Papers were categorized based on nine key aspects, including author, publication year, country/state, objective, participants, cancer type, system name, system capabilities, and type of platform. Eligible studies were appraised using a mixed-methods appraisal tool (MMAT).ResultsAnalysis of 85 studies indicated a diverse range of electronic Patient-Reported Outcome systems and platforms in cancer care, Notably, PRO-CTCAE and CHES were frequently cited for their roles in data collection and analysis. Moreover, web-based platforms were predominant, followed by mobile-based and computer-based systems. In addition, Symptom assessment and management emerged as significant capabilities in the utilization of these systems for oncology care.ConclusionOur systematic review of electronic patient-reported outcome (ePRO) systems in cancer care focused on the capabilities of these systems for capturing patient data and improving cancer treatment outcomes. This study emphasized the potential of electronic systems to enhance patient-centred oncology practices and optimize cancer care delivery.